Direct manipulation of liquid ordered lipid membrane domains using optical traps - Friddin,M; Bolognesi,G; Salehi-Reyhani,A; Ces,O; Elani,Y (Communications Chemistry, 2019)
Multicomponent lipid bilayers can give rise to coexisting liquid domains that are thought to influence a host of cellular activities. There currently exists no method to directly manipulate such domains, hampering our understanding of their significance. Here we report a system that allows individual liquid ordered domains that exist in a liquid disordered matrix to be directly manipulated using optical tweezers. This allows us to drag domains across the membrane surface of giant vesicles that are adhered to a glass surface, enabling domain location to be defined with spatiotemporal control. We can also use the laser to select individual vesicles in a population to undergo mixing/demixing by locally heating the membrane through the miscibility transition, demonstrating a further layer of control. This technology has potential as a tool to shed light on domain biophysics, on their role in biology, and in sculpting membrane assemblies with user-defined membrane patterning.